Agrarian Problems Ahead of the 1955 General Elections in Medan City - Hasibuan, Jean Ari; Saragih, Mujahid Widian; Hasibuan, Yandi Syaputra; Anshari, Andry (Talenta Publisher, 2023)
This article discusses the agrarian problems that occurred in Medan ahead of the 1955 General Election. The agrarian problem stems from Dutch plantation activities in East Sumatra which required a lot of vacant land to become an industrial center, including Medan being a victim. In its development, many people were deliberately brought in to fill this area. During the Japanese occupation, the plantation lands were replaced for logistical needs by people from outside Medan who were organized by the Japanese to occupy the lands. The succession of power occurred again, the occupied lands then became a source of problems and gave birth to conflicts between stakeholders. This situation is then used as material by political parties that will contest the General Election by supporting one of the parties. This article is only limited to agrarian issues ahead of the 1955 Election in Medan City. Of course, it is very possible that there are similar articles that discuss the development of agrarian issues in subsequent elections, both in Medan City, and Indonesia in general.